An ERP Study of Emotional Face Processing in the Adult and Infant Brain. - Leppänen, Jukka M.; Vogel-Farley, Vanessa K.; Moulson, Margaret C. (Child Development)
To examine the ontogeny of emotional face processing, event-related potentials (ERPs) were recorded from adults and 7-month-old infants while viewing pictures of fearful, happy, and neutral faces. Face-sensitive ERPs at occipital temporal scalp regions differentiated between fearful and neutral/happy faces in both adults (N170 was larger for fear) and infants (P400 was larger for fear). Behavioral measures showed no overt attentional bias toward fearful faces in adults, but in infants, the duration of the first fixation was longer for fearful than happy faces. Together, these results suggest that the neural systems underlying the differential processing of fearful and happy/neutral faces are functional early in life, and that affective factors may play an important role in modulating infants' face processing. Copyright 2007 by the Society for Research in Child Development, Inc. All rights reserved.